Awareness of Chronic Kidney Disease among General Adult Population in Indonesia - Susi Ari Kristina; Laksmy Anggun Larasati; Suci Hanifah (Journal of Global Pharma Technology, 2020)
Background: Chronic kidney disease (CKD) is rapidly becoming a major problem for developing countries such as Indonesia in terms of complicated management such as hemodialysis, continuous ambulatory peritoneal dialysis (CAPD) or high-cost renal transplantation. In its initial stages, early diagnosis and management of CKD may help avoid or delay disease progression. This study aimed to assess CKD's awareness and knowledge in Indonesia's general population. Methods: Cross-sectional research design was performed among the general adult population in Yogyakarta province. Recruiting participants using a convenience sample. A pre-validated questionnaire consisted of two parts, demographic features and CKD information. A logistic bivariate regression was used to identify independent CKD predictors, and p-value